Effect of Inclination Changes in High-Intensity Interval Training on Quality of Life of Male with Overweight and Obesity - natanael sinulingga; Sri Mardjiati Mei Wulan; Noor Idha; Sony Wibisono (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Overweight and obesity are major public health concerns globally and cause poor quality of life. Physical exercise plays a major role in reducing body weight, however, lack of time for exercise leads to a lack of regular exercise. High-intensity interval training (HIIT) is proposed as an alternative exercise in dealing with overweight and obesity and ultimately increases the quality of life. Aim: To proposed as an alternative exercise in dealing with overweight and obesity and ultimately increases the quality of life. Material and Methods: A randomized-controlled trial was conducted in a rehabilitation outpatient clinic. Twenty-two subjects with overweight or obesity were randomly allocated into the intervention and control group. The intervention group received HIIT using a treadmill (HR rest + 80-90% HR reserve) with inclination changes for 30 minutes (preceded by warming up and ending with cooling, 5 minutes each), 3 times a week, for 2 weeks. The Control group received no intervention. Change of quality of life was assessed by using SF-36 before and after the intervention. Results: Subjects’ baseline body height, body weight, BMI, VO2Max, and SF-36 on both groups showed no significant differences (p<0.05). Subjects in the control group are older than the intervention group (34.82±3.09 vs 30.36±2.58, p=0.002). Significant improvement of SF-36 was found only in domains of physical function in the intervention group (p=0.02). However,he between-group comparison analysis showed no difference of SF-36 Δ Value between groups. Conclusion: High-intensity interval training can be proposed as an exercise therapy option to improve the quality of life of males with overweight and obesity. It is necessary to do further research on HIIT with a larger number of samples, longer time, group training, and combined with other exercises.